Rapid and Efficient Differentiation of Human Pluripotent Stem Cells into Intermediate Mesoderm That Forms Tubules Expressing Kidney Proximal Tubular Markers - Lam, Albert Q. (American Society of Nephrology, 2014)
Human pluripotent stem cells (hPSCs) can generate a diversity of cell types, but few methods have been developed to derive cells of the kidney lineage. Here, we report a highly efficient system for differentiating human embryonic stem cells and induced pluripotent stem cells (referred to collectively as hPSCs) into cells expressing markers of the intermediate mesoderm (IM) that subsequently form tubule-like structures. Treatment of hPSCs with the glycogen synthase kinase-3β inhibitor CHIR99021 induced BRACHYURY(+)MIXL1(+) mesendoderm differentiation with nearly 100% efficiency. In the absence of additional exogenous factors, CHIR99021-induced mesendodermal cells preferentially differentiated into cells expressing markers of lateral plate mesoderm with minimal IM differentiation. However, the sequential treatment of hPSCs with CHIR99021 followed by fibroblast growth factor-2 and retinoic acid generated PAX2(+)LHX1(+) cells with 70%–80% efficiency after 3 days of differentiation. Upon growth factor withdrawal, these PAX2(+)LHX1(+) cells gave rise to apically ciliated tubular structures that coexpressed the proximal tubule markers Lotus tetragonolobus lectin, N-cadherin, and kidney-specific protein and partially integrated into embryonic kidney explant cultures. With the addition of FGF9 and activin, PAX2(+)LHX1(+) cells specifically differentiated into cells expressing SIX2, SALL1, and WT1, markers of cap mesenchyme nephron progenitor cells. Our findings demonstrate the effective role of fibroblast growth factor signaling in inducing IM differentiation in hPSCs and establish the most rapid and efficient system whereby hPSCs can be differentiated into cells with features characteristic of kidney lineage cells.